Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T22:29:21+01:00
1
a) 3x - 5 = 6+x
3x-x = 6+5
2x = 11 / :2
x = ¹¹/₂
x = 5 ½

b) 4x + 9 = 3x -7
4x-3x = -7-9
x = -16

c) 3-2x=4-2x
-2x+2x = 4-3
0 = 1

d) 7(2-3x) = 4x +5
14-21x = 4x+5
-21x-4x = 5-14
-25x = -9 / : (-25)
x = ⁹/₂₅

2
a)(3-2x)-(x+4) - (2x+5)=(3x-4)-(5x+7)
3-2x-x-4 -2x-5 = 3x-4-5x-7
-2x-x-2x-3x+5x = -4-7-3+4+5
-3x = -5 / :(-3)
x = ⁵/₃
x = 1 ⅔

b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4 = -2x+3-x-7
-x-2x+x+2x+x = 3-7-4+3+4
x = -1
2010-03-14T22:31:01+01:00
1
a) 3x - x = 6+5
2x=11 / :2
x = 5,5
b) 4x - 3x = - 7 - 9
x = -16

c) -2x+2x = 4-3
0=1 sprzeczne
d) 14 - 21 x = 4x +5
-21x-4x = 5-14
-25x = - 9 /: -25
x = 9/25

2.a)(3-2x)-(x+4) - (2x+5)=(3x-4)-(5x+7)
3-2x - x-4 -2x-5=3x - 4 -5x-7
-2x-x-2x-3x+5x = -4-7+5+4-3
-3x = -5/:-3
x = 5/3 = 1 2/3

b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x -2x-3 +x -4 = -2x+3-x-7
-x-2x+x+2x+x=3-7-4+3+4
x= -1


2010-03-14T22:34:12+01:00
Zad.1
a) 3x - 5 = 6+x
3x-x=6+5
2x=11 /:2
x=11/2
x=5 i 1/2

b) 4x + 9 = 3x -7
4x-3x=-7-9
x=-16

c) 3-2x=4-2x
-2x+2x=4+3
0=7 równanie sprzeczne.

d) 7(2-3x) = 4x +5
14-21x=4x+5
-21x-4x=5-14
-25x=-9 /:(-25)
x=9/25

Zad.2
a)(3-2x)-(x+4) - (2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
-2x-x-2x-3x+5x=-3+4+5-4-7
-3x=1 /:(-3)
x=-1/3

b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
-x-2x+x+2x+x=-4+3+4+3-7
x=-1

;))